Persona modelling using mix method segmentation in children computer interaction educational gamification / Nor Haniza Mohd Khir - Mohd Khir, Nor Haniza (2023)
Gamification has been widely used to solve issues in motivating and engaging students using technology for educational purposes. It is fun with regard to children’s nature. However, designing the gamification is more complicated than simply adding some game aspects to the kids-friendly application. Children computer interaction (C-CI) was developed to cater to children's particular demands. According to studies, lack of research on gamification for students ranging from 6-12 years old makes it difficult to see the positive effect of gamification on their educational achievement. Thus, this research aims to model user persona via identified game elements for the middle childhood. The use of persona optimize the usability of the designed system rather than focusing on users to change their way of acting. It focus on user’s behaviors, goals and attitudes when using gamification for learning. This research adopted a five phase’s methodology. First phase is to understand the behaviour of the middle-aged children in educational games. A preliminary data collection via interview and observation sessions were conducted.